2009
DOI: 10.1111/j.1365-2982.2009.01369.x
|View full text |Cite
|
Sign up to set email alerts
|

Salvinorin A inhibits colonic transit and neurogenic ion transport in mice by activating κ‐opioid and cannabinoid receptors

Abstract: The major active ingredient of the plant Salvia divinorum, salvinorin A (SA) has been used to treat gastrointestinal (GI) symptoms. As the action of SA on the regulation of colonic function is unknown, our aim was to examine the effects of SA on mouse colonic motility and secretion in vitro and in vivo. The effects of SA on GI motility were studied using isolated preparations of colon, which were compared with preparations from stomach and ileum. Colonic epithelial ion transport was evaluated using Ussing cham… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
81
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 64 publications
(88 citation statements)
references
References 41 publications
7
81
0
Order By: Relevance
“…Among others, our group demonstrated in vitro that SA inhibited electrically evoked twitch contractions of mouse stomach, ileum, and colon in a concentration-dependent manner (Fichna et al, 2009a). In all tissues studied, the effect of SA was blocked by the universal opioid antagonist naloxone and a selective k-opioid receptor (KOR) antagonist, nor-binaltorphimine (nor-BNI), which was in good agreement with classic binding assays (Capasso et al, 2006).…”
Section: Introductionsupporting
confidence: 61%
See 4 more Smart Citations
“…Among others, our group demonstrated in vitro that SA inhibited electrically evoked twitch contractions of mouse stomach, ileum, and colon in a concentration-dependent manner (Fichna et al, 2009a). In all tissues studied, the effect of SA was blocked by the universal opioid antagonist naloxone and a selective k-opioid receptor (KOR) antagonist, nor-binaltorphimine (nor-BNI), which was in good agreement with classic binding assays (Capasso et al, 2006).…”
Section: Introductionsupporting
confidence: 61%
“…Additionally, in the ileum and the colon, the inhibitory effect of SA was blocked by selective antagonists of cannabinoid type 1 (CB1) [N-(piperidin-1-yl)-5-(4-iodophenyl)-1-(2,4-dichlorophenyl)-4-methyl-1H-pyrazole-3-carboxamide, AM 251] and cannabinoid type 2 (CB2) [6-iodo-2-methyl-1-[2-(4-morpholinyl)ethyl]-1H-indol-3-yl](4-methoxyphenyl)methanone (AM 630)] receptors. In the in vivo studies, it has been shown that SA slowed upper intestinal transit, as indicated by a lower geometric center (GC) of the upper GI tract (Fichna et al, 2009a) and colonic motility (Fichna et al, 2009a), and inhibited GI motility in croton oil-induced intestinal inflammation in mice (Capasso et al, 2008). Moreover, Guida et al (2012) have shown that SA reduces mechanical allodynia induced by peripheral formalin injection in mice.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations